Bullard TALENT Kindergarten Christmas Show - Watkins, Howard::::::::: (1988)
Singers standing, dancers on stage; Robin Watkins in red dress looking at camera; Sarah Lackey behind mic stand center; Ms. ? In green coat; Ms. In red coat